2012
DOI: 10.1111/nmo.12018
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with successful decrease and discontinuation of antegrade continence enemas (ACE) in children with defecation disorders: a study evaluating the effect of ACE on colon motility

Abstract: Background Antegrade continence enemas (ACE) have been used in the treatment of defecation disorders in children; little is known on their effect on colon motility and the utility of the colon manometry (CM) predicting long term ACE outcomes. Methods Retrospective review of children with constipation undergoing CM before and after ACE to evaluate CM changes and their utility on predicting ACE outcome. Results 40 patients (mean age 8.8 SD 3y and 53% female) were included; 39/40 responded to the ACE. Of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 16 publications
3
58
1
Order By: Relevance
“…However, it has also been shown that findings of dysmotility are potentially reversible and that motility as measured by colonic manometry can improve after decompression of the colon [36][37][38]. An improvement in colonic motility has also been demonstrated to occur in patients after using ACE [39]. This suggests that colonic dysmotility may not only contribute to the severity of the constipation but may also be a consequence of long-standing constipation, possibly because of fecal stasis and colonic distension which in turn may lead to suboptimal motor function.…”
Section: Colonic Manometry and Surgerymentioning
confidence: 95%
“…However, it has also been shown that findings of dysmotility are potentially reversible and that motility as measured by colonic manometry can improve after decompression of the colon [36][37][38]. An improvement in colonic motility has also been demonstrated to occur in patients after using ACE [39]. This suggests that colonic dysmotility may not only contribute to the severity of the constipation but may also be a consequence of long-standing constipation, possibly because of fecal stasis and colonic distension which in turn may lead to suboptimal motor function.…”
Section: Colonic Manometry and Surgerymentioning
confidence: 95%
“…It is possible that this phenomenon has a multifactorial etiology and that the different clinical features are influenced by each other. This question cannot be completely answered based on the current studies, but it is important to note that dysmotility has been shown to improve after decompression of the colon in previous studies …”
Section: Discussionmentioning
confidence: 74%
“…Colon manometry can help guiding surgical interventions such as placement of an appendicostomy or a cecostomy for the administration of antegrade colonic enemas (ACE) or creation of a diverting ileostomy. Colonic manometry has been reported to be useful in predicting successful outcomes to ACE . The value of CM in guiding partial colonic resections is debated.…”
Section: Indicationsmentioning
confidence: 99%
“…Determine if a diverted colon may be re‐anastomosed . Clinical progress in combination with repeated CM testing are taken in consideration at the time of deciding which patients will benefit from reanastomosis or will require a resection. To assess the improvement of colonic dysmotility after long‐term use of ACE . Patients with poor response to ACE and abnormal colonic motility are likely to require a colonic resection.…”
Section: Indicationsmentioning
confidence: 99%